Coptic Christian Symbolism in Art as a Problem of Cultural Studies - D. Y. Pozdnyakova (MGIMO University Press, 2013)
In dialogue Coptic and Russian religious culture reveals value of the symbol letter Iota, the tenth letter of the Coptic alphabet, which begins the name of Jesus Christ. Symbols of letter writing is compared with pronouncing the name of Jesus and reading the prayer of Jesus